Genetic evaluation for TOR1-A (DYT1) in Brazilian patients with dystonia - Carlos Henrique F. Camargo; Sarah Teixeira Camargos; Salmo Raskin; Francisco Eduardo C. Cardoso; Hélio Afonso G. Teive (Arquivos de Neuro-Psiquiatria)
Several genes have been mapped in families or in sporadic cases of dystonia. TOR1-A (DYT1) gene was linked to isolated dystonia. Objective To associate clinical information of patients with dystonia with the TOR1-A gene mutations. Method Eighty-eight patients with dystonia in cervical area (focal, segmental, multifocal and generalized) were recruited at Movement Disorders Clinic of Hospital de Clínicas of the Federal University of Paraná between June of 2008 and June of 2009. They were submitted to the clinical evaluation. DNA was extract from blood and submitted at analysis to TOR1-A mutations by PCR according standard protocols. Results Two patients had c.907GAGdel mutation on TOR1-A gene. These patients, with familial history of dystonia, started his symptoms by legs and had secondary generalization. Conclusion We can suggest that analysis for TOR1-A mutations should be performed only in patients with early onset, generalized and familial dystonia.